REKONSTRUKSI PEMIKIRAN YURIDIS INTEGRAL DALAM PEMBAHARUAN SISTEM HUKUM JAMINAN FIDUSIA BERPILAR PANCASILA - Sri Mulyani (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2010)
Review the renewal of national legal systems there are big problems in the national legal system that is ius constitutum (problem of "Law Enforcement) & ius constituendum (problem of" law reform / development "). Fiduciary, as one of national law in practice raises many legal issues including the lack of legal certainty and legal protection, conflict norms, norms inconsistencies and disclaimers norm by economic actors in Fiduciary Law which causes ineffective in law enforcement. Reconstruction on fiduciary legal system becomes very urgent in the national legal reform for the realization of ideals of Pancasila pillared national law is the existence of legal certainty and justice for all stakeholders in economic activity.